Differing epidemiology of two major healthcare-associated meticillin-resistant Staphylococcus aureus clones - Jeremiah, C.; Kandiah, J.; Spelman, D.; Giffard, P.; Coombs, Geoffrey; Jenney, A.; Tong, S. (Elsevier, 2016)
Background: Two meticillin-resistant Staphylococcus aureus (MRSA) clones, sequence type (ST) 22 and ST239, have successfully spread globally. Across Australia, ST22 has supplanted ST239 as the main healthcare-associated MRSA. To understand the reasons underlying this shift, the epidemiology and clinical features of infections due to ST22 and ST239 MRSA isolates from a tertiary hospital in Melbourne, Australia were compared. Methods: Over six months, consecutive MRSA isolates with clinical data were collected from specimens referred to Alfred Health Pathology (AHP). Isolates were genotyped by a multi-locus-sequence-typing-based high-resolution melting method. Findings: Three hundred and twenty-eight of 1079 (30%) S. aureus isolated by AHP were MRSA. Of these, 313 were genotyped; 78 (25%) were clonal complex (CC) 22 (representing ST22) and 142 (45%) were CC239 (representing ST239). Common clinical syndromes included skin or soft tissue, respiratory tract and osteo-articular infections. On multi-variate logistic regression, compared with CC239, CC22 was associated with older patients [adjusted odds ratio (aOR) 1.04 for each year increase, 95% confidence interval (CI) 1.02-1.07)], and patients from subacute hospitals (aOR 2.7, 95% CI 1.2-5.8) or long-term care facilities (LTCFs; aOR 5.5, 95% CI 2.0-14.5). Median time from patient admission to MRSA isolation was nine days for CC239 and one day for CC22 (< 0.01). MRSA strain epidemiology varied according to hospital unit. Conclusions: CC22 and CC239 MRSA have differing ecological niches. CC22 is associated with elderly patients in LTCFs, and CC239 is associated with nosocomial acquisition. Infection control strategies involving LTCFs and their residents will likely be required to achieve continued MRSA control.